2023
DOI: 10.3390/life13071525
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Age at Menarche Gene Polymorphisms Are Associated with Offspring Birth Weight

Yuliya Reshetnikova,
Maria Churnosova,
Vadim Stepanov
et al.

Abstract: In this study, the association between maternal age at menarche (AAM)-related polymorphisms and offspring birth weight (BW) was studied. The work was performed on a sample of 716 pregnant women and their newborns. All pregnant women underwent genotyping of 50 SNPs of AAM candidate genes. Regression methods (linear and Model-Based Multifactor Dimensionality Reduction (MB-MDR)) with permutation procedures (the indicator pperm was calculated) were used to identify the correlation between SNPs and newborn weight (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 159 publications
1
18
0
Order By: Relevance
“…The present study revealed associations of rs12444979 GPRC5B with FGR both independently (the T allele of this SNPs was risky for FGR, OR = 1.56–1.67) and as part of SNP interactions models (50% of FGR risk models included this SNPs). Also, in our previously performed genetic study in this population (Russian women of Central Russia), the relationship of maternal rs12444979 GPRC5B (as part of interloci “dialogue” models) with offspring birth weight (BW) [ 40 ] was shown. rs12444979 GPRC5B was AAM-bounded [ 41 , 42 ] and BMI-involved [ 43 , 44 , 45 , 46 ], wherein the T allele of this SNP correlated with a later AAM [ 41 ], and an alternative genetic variant for it, the C allele, was associated with increased BMI [ 43 , 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study revealed associations of rs12444979 GPRC5B with FGR both independently (the T allele of this SNPs was risky for FGR, OR = 1.56–1.67) and as part of SNP interactions models (50% of FGR risk models included this SNPs). Also, in our previously performed genetic study in this population (Russian women of Central Russia), the relationship of maternal rs12444979 GPRC5B (as part of interloci “dialogue” models) with offspring birth weight (BW) [ 40 ] was shown. rs12444979 GPRC5B was AAM-bounded [ 41 , 42 ] and BMI-involved [ 43 , 44 , 45 , 46 ], wherein the T allele of this SNP correlated with a later AAM [ 41 ], and an alternative genetic variant for it, the C allele, was associated with increased BMI [ 43 , 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…(our in silico materials). In previous studies, rs7538038 KISS1 was linked with AAM (the G allele was a genetic factor of early AAM) [ 53 ], central precocious puberty in girls (allele G was risky for central precocious puberty) [ 54 ], BW and endometrial hyperplasia (as part of inter-genic interworkings, [ 31 , 40 ], respectively). So, we can generalize that the AAM-reducing allele G rs7538038 KISS1 , also associated with central precocious puberty of girls, is an FGR-protective factor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations